Postmodern Paradox: Artificial Intelligence, Pedagogy and the Return of Robot Slavery - Dennis, Jeremy (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
Despite the contributions that postmodernism has made to teaching and learning in the computer age, several scholars and practitioners in education persist in proclaiming its demise or death. This philosophical survey challenges this argument by recalibrating Jacques Derrida’s and Jean-François Lyotard’s contributions to postmodern thought as complementary meditations on the simultaneity of differences. With this reset in mind, one discovers that the evidence critics use to substantiate the end of postmodernism in education is often tenuous and paradoxical. In fact, the simultaneity and indeterminacy at the core of postmodern thinking make it indispensable in contemporary debates on the dichotomy between human and non-human entities, especially as artificial intelligence and robots become increasingly efficient partners and rivals in our classrooms and workplaces. While robot slavery has been introduced as a resolution to the binary opposition between humans and non-humans, postmodernism reminds us that this remedy is contentious and not new. Before robots such as Figure 02 and Mobile ALOHA, there was Rastus Robot, a technological innovation that courts the idea of a black mechanical slave. This study reveals how postmodernism and technological advancements continue to inform our conversations about education and trouble the border between humans and the robot slaves of tomorrow.